Upaya Peningkatan Preventif dan Rehabilitatif dalam Mengontrol Gula Darah - rizky wulandari (Universitas Muhammadiyah Palembang, 2025)
Elderly people over 50 years of age are at risk of developing degenerative diseases, one of which is diabetes mellitus. Complications of diabetes mellitus, if not properly managed, will cause disorders of the blood vessels, both macrovascular and microvascular, disorders of the nervous system or what is known as neuropathy. This complication occurs in people with diabetes mellitus who have had a long time or who have just been diagnosed with DM. Macrovascular complications of diabetes mellitus occur in the heart, brain, and blood vessels. Microvascular disorders occur in the eyes and kidneys, neuropathy complaints can also be experienced by people with DM in the form of motor, sensory, and autonomic neuropathy. Community service activities were carried out in May 2025 in the Sendnag Mulyo sub-district, Sleman, Yogyakarta, attended by 20 elderly people with the approach taken in the form of socialization and carrying out low-impact aerobic exercise. This activity focuses on the elderly's understanding of diabetes mellitus, containing material on diabetes mellitus, risk factors, the impact of diabetes mellitus, and how to prevent it with low-impact aerobic exercise. The results of the pre- and post-tests from this community service activity showed that participants were able to increase their knowledge about blood sugar levels and learn alternative ways to manage blood sugar through low-impact aerobic exercise.